Influence Of Financial Literacy And Financial Management Behavior Among Students Of UIN Smh Banten - Annisa Nurrohmah Azzahra; Fadia Aulia; Faiza Dara Ayuningtiyas; Wahyu Hidayat; Zaini Ibrahim (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
From survey data conducted by the Financial Services Authority regarding national finance, the financial literacy index in Banten is still below the national average of 45.19 percent. This was conveyed directly by the Head of OJK Jabodetabek and Banten Province in 2022. The low financial literacy index in Banten, OJK invites to jointly improve finance in the community, especially in students. Financial literacy is knowledge, skills, beliefs that influence a person's financial attitudes and behavior to improve the quality of decision making and financial management in order to achieve prosperity. This study uses a survey method in collecting answers from respondents. Using 50 samples of students at Banten State Islamic University who were randomly selected. The results of data collection through questionnaires that will be processed and analyzed using linear regression statistical methods. Based on this, it was found that financial literacy with indicators of basic knowledge of personal finance, personal financial records, and financial behavior had an effect on student financial management.